THE INFLUENCE OF RISK GOVERNANCE ON COMPANY PERFORMANCE - Rina Melsyawati; Juniati Gunawan; Idrianita Anis (JRAK, 2022)
Banking can give an impact on the economic sector's improvement; if the banking sector is healthy, a nation's financial industry can also be regarded as beneficial. The OJK study indicates a decrease in bank credit compared to the previous year when it reached 11.7 per cent. This study aims at elucidating the empirical evidence that risky governance affects the performance of financial and banking firms. Panel data regression was used to analyze the data, and the sample consisted of banks listed on the IDX from 2017-2020. The findings of this study demonstrated that risk governance at the enterprise level, board-level control, and risk governance are affecting firm performance. The effectiveness of this research is that Management-Level RGOV tends to decrease profitability because of the additional costs related to its implementation. Financial regulators may find this a helpful result as feedback to evaluate the effectiveness of regulation and possible future improvements.